2020
DOI: 10.2147/oajsm.s232727
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Extracorporeal Shock Wave Therapy in the Treatment of Patients with Trigger Finger</p>

Abstract: Introduction: Trigger finger disorder is a sudden release or locking of a finger during flexion or extension. Regarding the complications and disadvantages mentioned for the methods used in the treatment of trigger finger disorder, the aim of this study was to investigate the effect of extracorporeal shock wave therapy in the treatment of patients with trigger finger. Methods: This study was an interventional study recruiting 19 patients with trigger finger disorder. Evaluation of pain severity, severity of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The severity grade may be an alternative for a non-invasive method such as steroid injection [28]. Another study found similar results in pain on the effectiveness of ESWT in trigger finger treatment [29].…”
Section: Discussionmentioning
confidence: 85%
“…The severity grade may be an alternative for a non-invasive method such as steroid injection [28]. Another study found similar results in pain on the effectiveness of ESWT in trigger finger treatment [29].…”
Section: Discussionmentioning
confidence: 85%
“…Any papers were selected in PEDro and Cochrane Library Databases. Of the four total papers one is an interventional study, 13 one is a retrospective cohort study, 14 and two are prospective RCTs. 7 , 15 …”
Section: Resultsmentioning
confidence: 99%
“…Two types of physical therapies were found to be used in the conservative management of trigger finger: external shock wave therapy (ESWT) in three papers, 13-15 and ultrasound therapy (UST) in one papers. 7 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations